Emerging Low-Dimensional Materials - Chen, Bo; Wang, Rutao; Wang, Nana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, we have a great collection of 11 outstanding articles that have been published. This Special Issue presents the recent progress on emerging low-dimensional materials and could encourage their future investigations. We hope that both researchers and the community in general can benefit from the outcomes of this Special Issue reprint.